"Cerdik" Family Assistance with Elderly Blood Pressure in RW 06 Tlogomas - Putri, Rona Sari Mahaji; Choeron, Rachmat Chusnul (Journal of Community Service for Health, 2024)
There are still many elderly who suffer from high blood pressure. The role of the family plays an important role in managing and controlling the blood pressure of the elderly. The aim of this community service was to determine the relationship of "CERDIK" family assistance and the blood pressure of the elderly. The design used a cross sectional, with the population being all elderly people living in RT 04 RW 06 Tlogomas, with a sample of 57 elderly people obtained through accidental sampling. The independent variable in this study is "CERDIK" family assistance, while the dependent variable is blood pressure. The instrument used a questionnaire. The data analysis used Spearman rank. The results showed that the majority of elderly people received good family assistance (52.6%); the majority of elderly people are pre-elderly (57.9%); and the results of statistical tests show that there was no relationship between CERDIK family assistance and elderly blood pressure. It is recommended that future researchers examine forms of family assistance (with family and elderly samples) which are associated with elderly people's blood pressure.